Considering the benefits of asphalt modification using a new technical life cycle assessment framework - Butt, Ali Azhar; Birgisson, Björn; Kringos, Niki (Journal of Civil Engineering and Management, 2016)
Asphalt mixtures properties can be enhanced by modifying it with additives. Even though the immediate benefits of using polymers and waxes to modify the binder properties are rather well documented, the effects of such modification over the lifetime of a road are seldom considered. To investigate this, a newly developed open technical life cycle assessment (LCA) framework was used to determine production energy and emission limits for the asphalt additives. The LCA framework is coupled to a calibrated mechanics based computational framework that predicts the in-time pavement performance. Limits for production energy of wax and polymers were determined for the hypothetical case studies to show how LCA tools can assist the additives manufacturers to modify their production procedures and help road authorities in setting ‘green’ limits to get a real benefit from the additives over the lifetime of a road. From the detailed case-studies, it was concluded that better understanding of materials will lead to enhanced pavement design and could help in the overall reduction of energy usage and emissions.First published online: 02 Sep 2015